2021
DOI: 10.1155/2021/6966041
|View full text |Cite|
|
Sign up to set email alerts
|

Braking Control System of Oilfield Minor Repair Machine Based on Wireless Sensor Network

Abstract: Traditional minor repair machines have low control efficiency and low automation. In order to improve the brake control efficiency of the oilfield minor repair machine, the oilfield minor repair machine brake control system based on wireless sensor network is designed. The front-end controller collects the data of the oilfield repair machine through the wireless sensor and realizes the communication between the sensor nodes and the data interaction with the communication node through the field bus inside the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…It was found that previous versions of this submission contained a figure unrelated to the topic of the paper and this graph was subsequently identified within several other submissions, all with accompanying text claiming to have generated the graph. A number of these submissions were rejected from the journal; however, 6 were published and have now been retracted from Security and Communication Networks and Scientific Programming [2][3][4][5][6].e authors responded to explain that an author from one of the identified submissions had provided copy editing for their manuscript and introduced the graph and accompanying text in error.e authors were unable to provide copies of correspondence to support their claim or the raw data from their study. e authors' explanation did not satisfy the concerns of the editorial board, and the article is therefore being retracted due to concerns with the reliability of the data.e authors do not agree to the retraction.…”
mentioning
confidence: 99%
“…It was found that previous versions of this submission contained a figure unrelated to the topic of the paper and this graph was subsequently identified within several other submissions, all with accompanying text claiming to have generated the graph. A number of these submissions were rejected from the journal; however, 6 were published and have now been retracted from Security and Communication Networks and Scientific Programming [2][3][4][5][6].e authors responded to explain that an author from one of the identified submissions had provided copy editing for their manuscript and introduced the graph and accompanying text in error.e authors were unable to provide copies of correspondence to support their claim or the raw data from their study. e authors' explanation did not satisfy the concerns of the editorial board, and the article is therefore being retracted due to concerns with the reliability of the data.e authors do not agree to the retraction.…”
mentioning
confidence: 99%
“…It was found that previous versions of this submission contained a gure unrelated to the topic of the paper and this graph was subsequently identi ed within several other submissions, all with accompanying text claiming to have generated the graph. A number of these submissions were rejected from the journal; however, 6 were published and have now been retracted from Security and Communication Networks and Scienti c Programming [2][3][4][5][6].e authors responded to explain that an author from one of the identi ed submissions had provided copy editing for their manuscript and introduced the graph and accompanying text in error.e authors were unable to provide copies of correspondence to support their claim or the raw data from their study. e authors' explanation did not satisfy the concerns of the editorial board, and the article is therefore being retracted due to concerns with the reliability of the data.e authors do not agree to the retraction.…”
mentioning
confidence: 99%
“…It was found that previous versions of this submission contained a gure unrelated to the topic of the paper and this graph was subsequently identi ed within several other submissions, all with accompanying text claiming to have generated the graph. A number of these submissions were rejected from the journal; however, 6 were published and have now been retracted from Security and Communication Networks and Scienti c Programming [2][3][4][5][6].…”
mentioning
confidence: 99%
“…It was found that previous versions of this submission contained a gure unrelated to the topic of the paper and this graph was subsequently identi ed within several other submissions, all with accompanying text claiming to have generated the graph. A number of these submissions were rejected from the journal; however, 6 were published and have now been retracted from Security and Communication Networks and Scienti c Programming [2][3][4][5][6].e authors responded to explain that an author from one of the identi ed submissions had provided copy editing for their manuscript and introduced the graph and accompanying text in error.e authors were unable to provide copies of correspondence to support their claim or the raw data from their study. e authors' explanation did not satisfy the concerns of the editorial board, and the article is therefore being retracted due to concerns with the reliability of the data.e authors do not agree to the retraction.…”
mentioning
confidence: 99%
“…It was found that previous versions of this submission contained a gure unrelated to the topic of the paper and this graph was subsequently identi ed within several other submissions, all with accompanying text claiming to have generated the graph. A number of these submissions were rejected from the journal; however, 6 were published and have now been retracted from Security and Communication Networks and Scienti c Programming [2][3][4][5][6].…”
mentioning
confidence: 99%